Tissue Hydrogen Peroxide Concentration Can Explain the Invasiveness of Aquatic Macrophytes: A Modeling Perspective - Asaeda, Takashi; Rashid, Md Harun; Schoelynck, Jonas (Frontiers in Environmental Science, 2021)
In recent years, an invasive macrophyte, Egeria densa, has overwhelmingly colonized some midstream reaches of Japanese rivers. This study was designed to determine how E. densa was able to colonize these areas, and to assess the environmental stresses that limit or even prevent colonization. Under experimental conditions, E. densa was kept in experimental tanks and in a flume, and tissue hydrogen peroxide (H2O2) concentrations were measured responding to either individual or multiple stresses of light intensity, low temperature, water flow velocity, and Fe ions. In addition, E. densa was sampled in rivers across Japan and environmental conditions were measured. The H2O2 concentration increased in parallel to the increment of environmental stress intensity, and the trend was independent of other stressors. These results highlight the potential efficacy of total H2O2 concentration as a proxy for the overall stress generated by stressors. Under increased H2O2 concentration, E. densa started first to decrease in chlorophyll concentration, then reduce its growth rate, and consequently reduce its biomass. The H2O2 concentration threshold, beyond which degradation is initiated, was between 15 and 20 mol/gFW, regardless of the stressor. However, longer exposure periods were required for the lower range of excessive H2O2 concentrations to achieve a similar reaction. In Japanese rivers, major stressors limiting E. densa colonization were identified as low water temperature, high solar radiation, and high water flow velocity. The relationship between stress intensity and H2O2 concentration was empirically determined. The results agreed with the observed lateral distribution of E. densa colonies in a river channel regarding high solar radiation inhibiting the colonization of E. densa in the shallow zones. Based on these results, we discuss the possibility of colonizing river reaches in different regions of Japan. In Western Japan, environmental stress predicted low H2O2 concentrations in E. densa, which would possibly allow for intense colonization. In Eastern and northern areas, the temperature is low enough for H2O2 concentrations to exceed the threshold, particularly in the early months, which would limit or even prevent E. densa colonization